2021
DOI: 10.1097/jan.0000000000000417
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cessation Programs for Pregnant Women

Abstract: Objective This study aimed to develop a Transtheoretical-Model-based and WhatsApp-text-message-supported smoking cessation program for pregnant women and to evaluate its effectiveness. Methods This study is a pretest–posttest designed, randomized controlled and quasi-experimental intervention research. The study was conducted on 50 pregnant women, 25 of them in the intervention group and 25 of them in the control group. A theory-based motivational indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This review encompasses a total of 19 studies, including four mobile telephone application studies: SmokeBeat (a smoking monitoring app), DynamiCare (a reward app), SmokeFree (a behavioural change-based app) and Tobbstop (a gaming app) 80–83. Additionally, 8 studies evaluated text messaging programmes that provided abstaining information, support and reminders: Scheduled Gradual Reduction or support with trans-theoretical model (TTM) psychological type support,84–86 SMS programme with usual care,87 88 Quit4baby89 and MiQuit 88 90 91. Two website-based programmes were included: Motiv8, which combined a contingency management component9 92 and MumsQuit, an automated and tailored cessation platform 93.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This review encompasses a total of 19 studies, including four mobile telephone application studies: SmokeBeat (a smoking monitoring app), DynamiCare (a reward app), SmokeFree (a behavioural change-based app) and Tobbstop (a gaming app) 80–83. Additionally, 8 studies evaluated text messaging programmes that provided abstaining information, support and reminders: Scheduled Gradual Reduction or support with trans-theoretical model (TTM) psychological type support,84–86 SMS programme with usual care,87 88 Quit4baby89 and MiQuit 88 90 91. Two website-based programmes were included: Motiv8, which combined a contingency management component9 92 and MumsQuit, an automated and tailored cessation platform 93.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies that measured the effect of DH interventions included self-reported abstinence77 78 80 86 92 95 or 7-day PPA 79 82 84 85 91 94 128 129. Five studies reported CA of various durations from 2 weeks to 140 days78 81 82 87 93 after starting the intervention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…logically follows. Existing tobacco cessation interventions oftentimes target an individual's readiness based on their stage of behavior change (as defined by the transtheoretical model of change [55]) and have proven to be effective in helping individuals reduce their nicotine intake [56,57]. In addition to the behavioral stage, our study enables the identification of the cognitive and behavioral state of individuals, as manifested in their peer interactions at a granularity that was not previously explored through incorporation of attributes that describe communication content and intent.…”
Section: Principal Resultsmentioning
confidence: 99%
“…Non-abstinent users making a promise to themselves or peers through the use of a commissive statement (eg, “I will stop smoking tomorrow.”) logically follows. Existing tobacco cessation interventions oftentimes target an individual’s readiness based on their stage of behavior change (as defined by the transtheoretical model of change [ 55 ]) and have proven to be effective in helping individuals reduce their nicotine intake [ 56 , 57 ]. In addition to the behavioral stage, our study enables the identification of the cognitive and behavioral state of individuals, as manifested in their peer interactions at a granularity that was not previously explored through incorporation of attributes that describe communication content and intent.…”
Section: Discussionmentioning
confidence: 99%